Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Evaluate the function [tex]g(x) = -2x^2 + 3x - 5[/tex] for the input values [tex]-2[/tex], [tex]0[/tex], and [tex]3[/tex].

1. For [tex]g(-2)[/tex]:
[tex]\[
\begin{array}{l}
g(-2) = -2(-2)^2 + 3(-2) - 5 \\
g(-2) = -2(4) + (-6) - 5 \\
g(-2) = -8 - 6 - 5 \\
g(-2) = \boxed{-19}
\end{array}
\][/tex]

2. For [tex]g(0)[/tex]:
[tex]\[
g(0) = -2(0)^2 + 3(0) - 5 \\
g(0) = 0 + 0 - 5 \\
g(0) = \boxed{-5}
\][/tex]

3. For [tex]g(3)[/tex]:
[tex]\[
g(3) = -2(3)^2 + 3(3) - 5 \\
g(3) = -2(9) + 9 - 5 \\
g(3) = -18 + 9 - 5 \\
g(3) = \boxed{-14}
\][/tex]


Sagot :

Let's evaluate the function [tex]\( g(x) = -2x^2 + 3x - 5 \)[/tex] for the input values [tex]\(-2\)[/tex], [tex]\(0\)[/tex], and [tex]\(3\)[/tex].

### Step-by-Step Solutions:

#### 1. Evaluating [tex]\( g(-2) \)[/tex]:
[tex]\[ g(-2) = -2(-2)^2 + 3(-2) - 5 \][/tex]
First, calculate [tex]\((-2)^2\)[/tex]:
[tex]\[ (-2)^2 = 4 \][/tex]
Now multiply by [tex]\(-2\)[/tex]:
[tex]\[ -2 \cdot 4 = -8 \][/tex]
Next, calculate [tex]\(3 \cdot (-2)\)[/tex]:
[tex]\[ 3 \cdot (-2) = -6 \][/tex]
Finally, sum all terms:
[tex]\[ g(-2) = -8 - 6 - 5 = -19 \][/tex]

So,
[tex]\[ g(-2) = -19 \][/tex]

#### 2. Evaluating [tex]\( g(0) \)[/tex]:
[tex]\[ g(0) = -2(0)^2 + 3(0) - 5 \][/tex]
First, calculate [tex]\(0^2\)[/tex]:
[tex]\[ 0^2 = 0 \][/tex]
Now multiply by [tex]\(-2\)[/tex]:
[tex]\[ -2 \cdot 0 = 0 \][/tex]
Next, calculate [tex]\(3 \cdot 0\)[/tex]:
[tex]\[ 3 \cdot 0 = 0 \][/tex]
Finally, sum all terms:
[tex]\[ g(0) = 0 + 0 - 5 = -5 \][/tex]

So,
[tex]\[ g(0) = -5 \][/tex]

#### 3. Evaluating [tex]\( g(3) \)[/tex]:
[tex]\[ g(3) = -2(3)^2 + 3(3) - 5 \][/tex]
First, calculate [tex]\(3^2\)[/tex]:
[tex]\[ 3^2 = 9 \][/tex]
Now multiply by [tex]\(-2\)[/tex]:
[tex]\[ -2 \cdot 9 = -18 \][/tex]
Next, calculate [tex]\(3 \cdot 3\)[/tex]:
[tex]\[ 3 \cdot 3 = 9 \][/tex]
Finally, sum all terms:
[tex]\[ g(3) = -18 + 9 - 5 = -14 \][/tex]

So,
[tex]\[ g(3) = -14 \][/tex]

### Final Results:
[tex]\[ \begin{array}{l} g(-2) = -19 \\ g(0) = -5 \\ g(3) = -14 \\ \end{array} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.